Producing ultra fine grain pure aluminum tubes using tubular channel angular pressing (TCAP) / Mohsen Mesbah - Mohsen, Mesbah (2013)
Poly-crystalline ultra fine grained and nano structured metallic materials have superior mechanical properties compared to conventional poly-crystalline metals. Therefore, many attempts in the past 20 years have been made to produce ultra fine grained and nano structured materials by many researchers around the world. Relatively large number of methods for producing bulk metallic materials ever offered, however, despite the widespread need for tubes with high strength to weight, less work is doing to produce ultra fine grained and nano structured tubes. In connection with the manufacturing of UFG tubes two methods of ASB and HPTT have already been provided. These procedures have disadvantages, such as; microstructure and strain inhomogeneity, requires complex and expensive equipment, large forces, adhesion between the layers and low Industrial capabilities. Therefore, providing an effective, inexpensive, with industrial capability and high productivity is required for tubes. Recently a novel method entitled Tubular Channel Angular Pressing (TCAP) has been developed by Faraji in 2011 in Iran who is consultant of current project. They have presented a method that is able to overcome most of the disadvantages of previous methods. Faraji et al have applied TCAP on AZ91 alloy but this method has not been applied on aluminum alloys. In this project this new method with the advantages of low cost, having no dimensional limitation for the tube, imposing severe plastic shear strain, high hydrostatic pressure and the ability to produce ultra-fine tubes and nanostructured metal tubes with high strength are applied to aluminum tubes for the first time. Ultrafine grained (UFG) cylindrical tubes were produced via recently developed tubular channel angular pressing (TCAP) through different passes from pure Aluminum. The microstructure and mechanical properties of processed tube through one to three passes of TCAP were investigated. Microstructural investigation shows notably decrease in the grain size to around 350 nm from the primary value of ~56 μm. Microhardness of the processed tube was increased to 49.4 Hv after one pass from an initial value of 32.9 Hv. An increase in the number of passes from 1 to higher number of passes has not more effect on the microhardness. Yield and ultimate strengths were increased 2.5 and 2.28 times compared to as cast condition. Notably increase in the strength was achieved after one pass TCAP while higher number of passes has not more effect.